Association of CYP19A1 Gene Polymorphism with Male Infertility in Khyber Pakhtunkhwa Population, Pakistan: CYP19A1 Gene Polymorphism and Male Infertility in Khyber Pakhtunkhwa - Alamgeer, Muhammad; Irfan, Muhammad; Ahmad, Irshad; Khan, Muhammad Fayaz; Rehman, Fahad Ur; Khan, Saifullah; Muhammad, Hafsah (Pakistan BioMedical Journal, 2026)
Male infertility is a multifactorial disease that is controlled by genetic, hormonal, and semen factors. In this research, the authors examined the relationship that exists between the CYP19A1 gene polymorphisms, semen parameters, and hormone profiles in male infertility. Objectives: To determine the Polymorphism CYP19A1 Gene and Male Infertility among the Khyber Pakhtunkhwa Population, Pakistan. Methods: 186 men were recruited into the study, consisting of 106 infertile men and 80 healthy controls. Sanger sequencing was done on three CYP19A1 SNPs (rs17703883, rs726546, and rs10046). ELISA was used to determine serum hormonal levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), prolactin, and testosterone, and semen parameters, such as sperm count, morphology, and motility. Results: Genotype and allele frequency analysis showed a significant relationship between male infertility and the polymorphisms of the following: rs 17703883 and rs 726546, and not the polymorphism of rs10046 (p>0.05). Nonetheless, none of the SNPs that were researched were significantly correlated with serum testosterone levels. Conclusions: These observations indicate that the same CYP19A1 gene (rs17703883 and rs726546) might have an implication on male infertility among this population, but they do not seem to be the cause of lowered serum testosterone. More research with an increased sample size and functional studies needs to be done to elucidate the functions of these variants. Additional studies on the genetic role of oestrogen metabolism in the occurrence of male infertility need larger samples and other functional variants of CYP19A1.